6-(3x-5)=7x-5

Simple and best practice solution for 6-(3x-5)=7x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-(3x-5)=7x-5 equation:


Simplifying
6 + -1(3x + -5) = 7x + -5

Reorder the terms:
6 + -1(-5 + 3x) = 7x + -5
6 + (-5 * -1 + 3x * -1) = 7x + -5
6 + (5 + -3x) = 7x + -5

Combine like terms: 6 + 5 = 11
11 + -3x = 7x + -5

Reorder the terms:
11 + -3x = -5 + 7x

Solving
11 + -3x = -5 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
11 + -3x + -7x = -5 + 7x + -7x

Combine like terms: -3x + -7x = -10x
11 + -10x = -5 + 7x + -7x

Combine like terms: 7x + -7x = 0
11 + -10x = -5 + 0
11 + -10x = -5

Add '-11' to each side of the equation.
11 + -11 + -10x = -5 + -11

Combine like terms: 11 + -11 = 0
0 + -10x = -5 + -11
-10x = -5 + -11

Combine like terms: -5 + -11 = -16
-10x = -16

Divide each side by '-10'.
x = 1.6

Simplifying
x = 1.6

See similar equations:

| -8+4x+6x=62 | | 2(4r+6)=8(r+2) | | 14x+12y=690 | | -3+7x-3x=-47 | | 4x-4+98=18x-4 | | 25=q-13 | | -2x-8+4x=4 | | 15=x+6x+8 | | a-4=34 | | X+28=110 | | -5p-14= | | -4/9+(-2.8)= | | -6-4x=-50 | | -5p+-14= | | (s/2)+8=54 | | p-4.8=6 | | 5.9v-1.3=2.3v+1.3 | | 2(3a+9)-30=3(2a-4) | | -443=8(9a-9)+5a | | 6n-4=n+19 | | (5/6)x=35 | | x(4+9)= | | -22=p+13.78 | | (7/9)x=42 | | X^3+5x+6x=0 | | 3x+6=-2+11 | | 6*8w=208 | | 6x+12=41 | | -(4/9)x=2/3 | | 16=f-12 | | 40=j-16 | | 3y-4.6=4y |

Equations solver categories